Impact of a social and behavior change campaign and volunteer malaria tester program on malaria care seeking among gold miners in Guyana - Sood, Suruchi; Beckles, Onika; Orkis, Jennifer; Wilson, Sean; Hunter, Gabrielle; Davis, TrishAnn; Hussain, Mona; James, Kashana (Frontiers in Communication, 2024)
The manuscript aligns with the journal's focus on health communication by detailing the implementation and impact of the volunteer malaria tester (VMT) program and the "Lil Mosquito, Big Problem" (LMBP) campaign in Guyana. These initiatives illustrate the effective use of social and behavior change (SBC) interventions to address malaria among migrant gold miners. Utilizing participatory human-centered design and the ideation model, the LMBP campaign addresses psychosocial determinants such as knowledge, attitudes, beliefs, and social norms. Surveys from 2019 and 2022 show increased knowledge, improved psychosocial factors related to malaria prevention and treatment, and higher prompt care-seeking levels among those exposed to both the VMT program and the SBC campaign. The manuscript emphasizes the importance of culturally appropriate, stakeholderengaged social and behavior change communicationhealth communication strategies adaptable to shifting contexts, such as changes in the mining population and economic difficulties. Additionally, it highlights the role of community involvement in enhancing the effectiveness and sustainability of s o c i a l a n d b e h a v i o r c h a n g e health communication interventions. The evidence-based results and the practical, theory-driven approach offer valuable insights for future interventions in similar settings and for other global health issues, demonstrating the wider relevance of effective s o c i a l a n d b e h a v i o r c h a n g e c o m m u n i c a t i o n health communication strategies.